2013
DOI: 10.5586/aa.2013.038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multi-nutrient complex fertilizers on growth and tuber yield of very early potato (Solanum tuberosum L.) cultivars

Abstract: A b s t r a c tThe aim of the study was to compare the effect of multi--nutrient complex fertilizers (HydroComplex, Nitrophoska Blue Special and Viking 13 from the nitrophoska group, and Polimag S from the amophoska group) and single-nutrient fertilizers on the growth and tuber yield of very early potato cultivars ('Aster', 'Fresco', 'Gloria'). The field experiment was carried out on podzolic soil in mid-eastern Poland during [2005][2006][2007]. The study showed a greater beneficial effect of HydroComplex and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…In this treatment, compared to complex fertilizers, the tuber yield was by 5.4-7.8% lower (P < 0.05), fewer large tubers (more than 6 cm) were formed, potatoes contained less starchy and accumulated more nitrates (P < 0.05) ( Table 2). Studies by Wadas and Dziugel (2013) on the effect of various complex and simple fertilizers on potato yield have also revealed that complex fertilizers, as compared with simple fertilizers, better enhance the development of the aboveground part and tubers, but of the tested complex fertilizers, only Nitrophoska Blue Special resulted in higher tuber yield, on average by 2.40 t ha -1 , compared with simple fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…In this treatment, compared to complex fertilizers, the tuber yield was by 5.4-7.8% lower (P < 0.05), fewer large tubers (more than 6 cm) were formed, potatoes contained less starchy and accumulated more nitrates (P < 0.05) ( Table 2). Studies by Wadas and Dziugel (2013) on the effect of various complex and simple fertilizers on potato yield have also revealed that complex fertilizers, as compared with simple fertilizers, better enhance the development of the aboveground part and tubers, but of the tested complex fertilizers, only Nitrophoska Blue Special resulted in higher tuber yield, on average by 2.40 t ha -1 , compared with simple fertilizers.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, Wadas et al , who investigated complex fertilizers containing manganese and boron among others (HyroComplex, Nitrophoska Blue Special, Viking 13, Polimag S), claimed that fertilizers had no influence on the accumulation of starch by very early cultivars. A cycle of trials testing the effect of mineral fertilizers applied in a dose of 360 kg/ha NPK with added micronutrients was also completed by Rainys and Rudokas , who demonstrated the absence of any effect of fertilization on starch accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…The weather conditions, atmospheric precipitation in particular, modify the quality of potato yields, especially the accumulation of starch .…”
Section: Methodsmentioning
confidence: 99%